1997
DOI: 10.1063/1.474307
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dumbbell structures of vanadium–C60 clusters

Abstract: Articles you may be interested inExperimental and theoretical studies on the electronic properties of vanadium-benzene sandwich cluster anions, V n Bz n+1 − (n = 1-5) J. Chem. Phys. 137, 224305 (2012); 10.1063/1.4769776 Formation, detection, and stability studies of neutral vanadium sulfide clustersElectronic and geometric structures of Co 2 C n − and V 2 C n − : Initial growth mechanisms of late and early 3d transition-metal carbide clusters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 20 publications
2
64
1
Order By: Relevance
“…In more recent times, both experiment and theory have explored gas-phase, transition metalorganic complexes with benzene, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] pyridine, 23 fullerenes, 7,22,[24][25][26][27][28][29][30][31][32] various polycyclic aromatic hydrocarbons ͑PAHs͒, 7,33-42 and 1,3,5,7-cyclooctatetraene 43 ͑COT͒ serving as organic moieties. In more recent times, both experiment and theory have explored gas-phase, transition metalorganic complexes with benzene, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%
“…In more recent times, both experiment and theory have explored gas-phase, transition metalorganic complexes with benzene, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] pyridine, 23 fullerenes, 7,22,[24][25][26][27][28][29][30][31][32] various polycyclic aromatic hydrocarbons ͑PAHs͒, 7,33-42 and 1,3,5,7-cyclooctatetraene 43 ͑COT͒ serving as organic moieties. In more recent times, both experiment and theory have explored gas-phase, transition metalorganic complexes with benzene, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%
“…The cluster building blocks used in the construction of our assemblies are metal-covered fullerenes. Several studies of clusters containing two or more fullerene molecules bonded with alkali metals [7] and transition metals [8][9][10][11][12] have already been reported. The metal we have chosen for the present study is thulium.…”
Section: Introductionmentioning
confidence: 99%
“…A Ni-C 60 -Ni-C 60 linear structure would seem unlikely, since the Ni 2 ͑C 60 ͒ 3 species would then be expected, but is not observed. Nikajima et al 15 observed V 2 ͑C 60 ͒ 3 at room temperature and attributed it to a linear C 60 -V-C 60 -V-C 60 structure. Nagao et al 16 also observed Sc 2 ͑C 60 ͒ 3 and Ti 2 ͑C 60 ͒ 3 and proposed similar structures for these species.…”
Section: Cluster Structuresmentioning
confidence: 99%
“…Clustering of C 60 around Au clusters has been reported in the deposition of Au on a film of C 60 . 3 Recent studies of the adsorption of C 60 molecules on small clusters of V, 15,16 Co, 17 Sc, 16 Ti, 16 and Cr, 16 have been re-ported using a pulsed laser vaporization technique for generating both the metal clusters and C 60 . Clusters containing up to five metal atoms were studied in most cases.…”
Section: Introductionmentioning
confidence: 99%